The impact of silver nanoparticles phytosynthesized with Viburnum opulus L. extract on the ultrastrastructure and cell death in the testis of offspring rats. (April 2021) - Bidian, Cristina; Filip, Gabriela Adriana; David, Luminita; Florea, Adrian; Moldovan, Bianca; Robu, Daniela Popa; Olteanu, Diana; Radu, Teodora; Clichici, Simona; Mitrea, Daniela-Rodica; Baldea, Ioana
Abstract: Aim: To investigate the effects of prenatal exposure to AgNPs obtained by green synthesis with Viburnum opulus L. extract on the testis in male offspring rats. Material and methods: Two different doses of AgNPs (0.8 and 1.5 mg/kg b.w.) and vehicle (PBS) were administered to Wistar female rats on days 3–14 of gestation. At 6 weeks after birth, the ultrastructural changes in correlation with the amount of silver as well as the parameters of oxidative stress, inflammation and cell death mechanisms in the testis of male offspring were evaluated. Results: AgNPs administered during pregnancy crossed the placental and testicular barriers and induced oxidative stress, DNA damage and autophagy as mechanism of cell toxicity. The markers of inflammation and apoptosis decreased after AgNPs exposure while the NFkB activation increased. TEM examination revealed important ultrastructural changes of Sertoli cells, numerous vacuoles and cytoplasmic changes suggestive of the cellʹs evolution towards necrosis. Conclusion: Phytoreduced silver nanoparticles with polyphenols from Viburnum opulus L. fruit extract, administered during the embryological development of the male gonad, have testicular toxic effects in offspring even at 6 weeks after birth. Highlights: Silver nanoparticles were administered to pregnant female on day 3–14 of gestation. The nanoparticles induced ultrastructural changes in the testis of male offspring. The nanoparticles exerted cytotoxic effect by lipid peroxidation and DNA lesions. The nanoparticles induced activation of autophagy and NFkB expression.